Imaging diagnosis in relapsing polychondritis and correlation with clinical and serological data - Thaiss, Wolfgang Maximilian; Nikolaou, K.; Spengler, W.; Spira, Daniel; Xenitidis, T.; Henes, J.; Horger, M. (Skeletal radiology, 2016)
We hypothesize that imaging findings from CT and MRI correlate better with clinical markers for assessment of disease activity in patients with the rare relapsing polychondritis (RPC) than with serological inflammatory markers.